Newborn screening for Duchenne muscular dystrophy: a psychosocial study. Issue 2 (1st March 2002) - Parsons, E P; Clarke, A J; Hood, K; Lycett, E; Bradley, D M
Abstract : Objective: To evaluate the psychosocial implications of newborn screening for Duchenne muscular dystrophy. Design: Prospective psychosocial assessment. Setting: Primary care. Respondents: Study: ( a ) families of an affected boy identified by screening (n = 20); ( b ) families of a boy with a transient screening abnormality (n = 18). Control: ( a ) families of a boy with a later clinical diagnosis (n = 16); ( b ) random sample of mothers of boys aged 6–9 months (n = 43). Interventions: Questionnaires and semistructured interviews. Main outcome measures: Attitudes to newborn screening and impact of screening on mother-baby relationship, anxiety/wellbeing, and reproductive patterning within families of an affected boy. Results: Most families of an affected boy were in favour of newborn screening on the grounds of reproductive choice and time to prepare emotionally and practically. There was no evidence of any long term disruption to the mother-baby relationship. Anxiety levels for the screened group were slightly above threshold but returned to normal during the period of the study. There was no evidence, from anxiety or wellbeing scores, that the transient group had suffered any disadvantage. Although the profile of the screened and later clinically diagnosed cohorts was similar after diagnosis, when boys from the screened cohort were 4 years old and more socially aware, their profile was more positive. There was evidence that reproductive patterning had been modified, and four fetuses carrying a mutation causing Duchenne muscular dystrophy were terminated. Conclusion: A case can be made for newborn screening provided that the test is optional, a rigorous protocol for service delivery is used, and an infrastructure providing continuing support is in place.